How flexible can inflation targeting be and still work? - Kenneth N. Kuttner; Adam S. Posen (Bank of England, External Monetary Policy Committee Unit, 2011)
This paper takes up the issue of the flexibility of inflation targeting regimes, with the specific goal of determining whether the monetary policy of the Bank of England, which has a formal inflation target, has been any less flexible than that of the Federal Reserve, which does not have such a target. The empirical analysis uses the speed of inflation forecast convergence, estimated from professional forecasters' predictions at successive forecast horizons, to gauge the perceived flexibility of the central bank's response to macroeconomic shocks. Based on this criterion, there is no evidence to suggest that the Bank of England's inflation target has compelled it to be more aggressive in pursuit of low inflation than the Federal Reserve.
Keywords: E42; E58; E65; 330; Inflation targeting; inflation expectations; monetary policy; Zentralbank; Geldpolitisches Ziel; Inflationssteuerung; Wirtschaftsprognose; Inflationserwartung; USA; Großbritannien